PENGARUH DIKLAT DAN PENGALAMAN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA KANTOR KECAMATAN NISAM KABUPATEN ACEH UTARA - SE, Muslim; Konadi, Win (JURNAL KEBANGSAAN, 2020)
The purpose of this study, 1) To Analyze the influence of education and training (training) on employee work productivity in Nisam District office, North Aceh District. 2) To analyze the effect of work experience on employee productivity, Nisam District office, North Aceh District, and 3) Analyze which factors are more dominant between education and training (diklat), and work experience on employee work productivity. The analysis results obtained that; 1). The level of achievement of education and training in supporting work is 80.28 percent. From these results it has shown an optimal level. 2). The level of achievement of work experience supports work by 81.39%. 3). The level of achievement of work productivity from expectations in employment is 81.56%. 4). The results of regression analysis showed that there was an effect of Diklat (X1) on Work Productivity (Y) of Employees in Nisam District Office, North Aceh District. And there is also the influence of work experience (X2) on work productivity (Y) of employees in Nisam District Office, North Aceh District. 5). Education and Training Effect (X1) is greater than Work Experience (X2) on Work Productivity (Y) Employees at Nisam District Office North Aceh District. 6). The results of the measure of correlation and determination are obtained; amounting to 83.4% contribution of the variable Training and Employee Work Experience on work productivity. 7). The results of the regression model between training and work experience on work productivity are Y = 2.174+ 0.660 X1 + 0.312 X2, so the model states; a). If the Education and Training Provider increases by 10 percent, then work productivity will increase by (0.660 x 10) = 6.60 percent. And b). If work experience support increases by 10 percent, then work productivity will increase by (0.312 x 10) = 3.12 percent. Keywords: Training, Work Experience, Work Productivity.